Occurrence of imposex in Thais haemastoma: possible evidence of environmental contamination derived from organotin compounds in Rio de Janeiro and Fortaleza, Brazil - Fernandez Marcos Antonio; Limaverde Aricelso Maia; Castro Italo Braga de; Almeida Ana Cristina Martins; Wagener Angela de Luca Rebello (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2002)
There are indications that the widespread use of organotin compounds (TBT and TPT) as antifoulings, as stabilizers in plastic and as pesticides, has severely affected several species of marine organisms. The most striking effect of TBT and TPT as hormonal disruptors is the development of male organs in females of gastropods, currently denominated imposex. This syndrome can lead to the sterilization and death of affected organisms. The present work gives an overview of the present state of knowledge on imposex occurrence and reports results of a survey conducted in Guanabara Bay, Rio de Janeiro and in several sites along the coast of Fortaleza, Ceará State. Different stages of imposex development were verified in this survey, however, the most prominent levels appeared associated to known spot sources of TBT and TPT.